Local Wisdom and Coastal Protection on Rupat Island: The Role of the Akit Indigenous Community - Zulfikar Jayakusuma; Maria Maya Lestari; Tengku Arif Hidayat; Ferawati Ferawati; Davit Rahmadan (Faculty of Law Universitas Lampung, 2026)
The Akit Tribe is an indigenous community inhabiting Rupat Island, one of Indonesia's outermost islands bordering the Strait of Malacca. Historically, the Akit people played an important role in safeguarding the maritime territory of the Siak Sultanate and continue to maintain local wisdom related to coastal and environmental management. This study examines the contribution of Akit local wisdom to environmental conservation and its relevance to protecting Indonesia's sovereignty in border areas. Using a qualitative approach supported by empirical field data, the study finds that traditional practices, particularly mangrove conservation and sustainable resource management, contribute to coastal protection and strengthen Indonesia's presence in strategically important maritime regions. The study also highlights the need for stronger legal recognition and protection of Akit customary institutions and traditional knowledge.